2017
DOI: 10.1007/s13197-017-2713-6
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme activity, amino acid profiles and hydroxymethylfurfural content in Ethiopian monofloral honey

Abstract: The enzymes activity, hydroxymethylfurfural (HMF) and amino acids in honeys are relatively low. However, they play very significant role for honey quality. In this study, enzymes, amino acids and HMF contents of Ethiopian monofloral honeys were investigated. Diastase, invertase and HMF were analyzed based on the Harmonized International Honey Commission method and amino acids using amino acids analyzer (HPLC). Diastase activity ranged from 3.91 ± 0.730 () to 13.6 ± 2.30 [ (L: Lalibella)]; invertase 36.5 ± 1.93… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 35 publications
3
30
1
Order By: Relevance
“…According to [48], honey's enzyme content may differ based on the age of the bees that vary in race, the nectar gathering time, the colony's physiological period, the quantity of nectar flow and its sugar content and pollen consumption. The diastase enzyme activity of A. mellifera honey with extrafloral nectar was higher than the previous report on Azerbaijan honey (9.69 Schade units) [39], Ethiopian honey (13.60 Schade units) [49], and comparatively similar to Venezuelan honey (16.13 Schade units) [31] and Algerian honey (15.10 Schade units) [50].…”
Section: Resultscontrasting
confidence: 68%
“…According to [48], honey's enzyme content may differ based on the age of the bees that vary in race, the nectar gathering time, the colony's physiological period, the quantity of nectar flow and its sugar content and pollen consumption. The diastase enzyme activity of A. mellifera honey with extrafloral nectar was higher than the previous report on Azerbaijan honey (9.69 Schade units) [39], Ethiopian honey (13.60 Schade units) [49], and comparatively similar to Venezuelan honey (16.13 Schade units) [31] and Algerian honey (15.10 Schade units) [50].…”
Section: Resultscontrasting
confidence: 68%
“…A significant difference (p<0.05) was observed among the honey sample. Belay et al [ 73 ] reported the diastase activity of monofloral honey (4.94 ± 0.66 Schade units), which was in agreement with this finding. The difference in diastase activity depends on the nectar collection period, the physiological period of the colony, and pollen consumption [ 74 ].…”
Section: Resultssupporting
confidence: 79%
“…It decreases due to excessive storage and heating of honey [ 46 ]. Some honey types have also low diastase, naturally [ 73 ]. Diastase activities of Schefflera abyssinica and polyfloral honey of the current study were 4.10 ± 0.30 and 5.21 ± 0.17 Schade units, respectively ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…We noted that 100% of fresh honey samples studied contained ID ≥ 8 Schade units. The enzyme activity in honey from the same floral origin can possibly vary, due to the plant's nectar secretion quality and quantity, which was influenced by the contribution of the environment and the presence of different geographical races of bees, which is mainly governed by biotic and abiotic factors (Adgaba et al, 2017;Belay et al, 2017).…”
Section: Effect Of Heating On Hmf Contentsmentioning
confidence: 99%